EFEKTIFITAS MODUL ELEKTRONIK TERINTEGRASI MULTIPLE REPRESENTATION PADA MATERI IKATAN KIMIA - Ramdhani, Eka Putra; Khoirunnisa, Fitriah; Siregar , Nur Asti Nadiah (Journal of Research and Technology, 2020)
This research aimed to categorize the results of an electronic module effectiveness that integrated by multiple representation on chemical bonding. The research approach used in this research was descriptive quantitative. The effectivity results of N-Gain pretest and posttest of students critical thinking skills in the control class were 0.3 with the low category and the experimental class were 0.6 in the medium category, and the results of independent t-test on sig. (2-tailed) of 0.047<0.05, it meant that there were significant differences between the results of the control and experimental classes. Based on the results of study, it was found that the electronic module integrated multiple representation of high school chemistry learning in chemical bonding material was effective to be used in the learning process.